DETERMINANTS OF GREEN FDI: A CASE STUDY OF TOP FOREIGN COUNTRY INVESTORS IN INDONESIA - Riga Sanjaya; Ghazali Syamni; Husaini; Darmawati Muchtar; Jummaini; Aiyub (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the determinants of Green Foreign Direct Investment (Green FDI) in Indonesia by examining the effects of energy subsidies and the globalization index on Green FDI inflows. Panel data from six major investor countries during the 2020–2024 period were employed to test the research hypotheses. The results indicate that both energy subsidies and the globalization index have a positive and significant effect on Green FDI in Indonesia. These findings suggest that government policies supporting renewable energy and facilitating global economic integration play a key role in attracting environmentally sustainable investment. The study provides policy implications for decision-makers aiming to promote renewable energy development and advance Indonesia’s transition toward a low-carbon economy.